(:unas) unassigned - (:unkn) unknown (My University, 2025)
The aim of the article is to empirically find out the specifics of the correlation between the decision-making process and the personal qualities of representatives of various professions in the face of social instability. The study used the Melbourne Decision Making Questionnaire (MDMQ) and the Freiburg Personality Inventory (FBI). The hypothesis that decision-making processes are related to personal qualities and differ among representatives of different professions in the face of social instability was confirmed. It was found that the respondents mostly prefer a rational way of making decisions. However, a fifth of the respondents are characterized by the dominance of the avoidance strategy. No persons with pronounced procrastination were found. Doctors and programmers have emotional control and reduced aggressive reactions in the decision-making process. Social orientation of life choices is typical for teachers. IT specialists often use the avoidance strategy. Conclusions: In general, the peculiarities of decision-making strategies in the conditions of war are determined, which can be extrapolated to similar situations of military instability on the planet. The obtained results can be used in the process of developing programmes of professional development and psychological assistance of individuals in times of war. Research prospects may be the study of the gender aspect of decision-making.
Keywords: Avoidance, Decision-Making, Over-Vigilance, Personal Qualities, Individual Psychological Features, Procrastination, Vigilance, Aggression